Deep Brain Stimulation in the treatment of disorders of consciousness - Olszak, Joanna; Zalewa, Karolina; Bartoszek, Lidia; Orłowska, Dominika; Kapłan, Wojciech; Poleszczuk, Mikołaj; Poleszczuk, Karol; Milewska, Alicja; Czuba, Anna; Kaus, Marta (Journal of Education, Health and Sport, 2025)
Introduction and Purpose Disorders of consciousness, such as the vegetative state (VS) and minimally conscious state (MCS), are significant neurological conditions where patients exhibit limited or no awareness of their surroundings. Despite advancements in medical care, treatment options for these conditions remain limited, and prognosis is often poor. Deep brain stimulation (DBS) has emerged as a promising therapeutic option, particularly for patients with MCS or severe brain injuries. This review explores the clinical applications, and outcomes of DBS in the treatment of disorders of consciousness. Material and Methods A comprehensive literature review was conducted using the PubMed database, focusing on articles published up to the end of 2024. The search included the keywords "deep brain stimulation", "disorders of consciousness", "neuromodulation therapy", and " effectiveness" in various combinations. Relevant studies were selected based on criteria such as the effect of DBS in patients with disorders of consciousness. Results Several studies have shown that DBS, particularly targeting regions such as the thalamus or subthalamicnucleus, can lead to improvements in consciousness levels, responsiveness to external stimuli, and interaction with the environment. In some cases, patients in MCS have exhibited improved awareness, motor responses, and even the ability to communicate. Key factors influencing outcomes include the timing of DBS application, the extent of brain injury, and the specific brain regions targeted. Conclusions DBS offers a novel and potentially effective treatment for patients with disorders of consciousness, especially those in a minimally conscious state. While the results are promising, more controlled and larger-scale clinical trials areneeded to better understand the long-term efficacy, optimal timing, and appropriate patient selection.